PEMBERDAYAAN UKM DALAM PROMOSI WISATA EDUKASI: PENGEMBANGAN BROSUR INTERAKTIF DI DESA SUGIHAN KABUPATEN SEMARANG - Zusrony, Edwin; Edy Jogatama Purhita; Endang Kustami; Agustinus Budi Santoso; Indra Ava Dianta; Widya Ariyani; Greget Widhiati; Jarot Dian Susatyono; Ida Hendriyani; Siti Kholifah; Haryo Kusumo (LPPM ITB AAS Indonesia Surakarta, 2025)
This community service activity aims to empower Small and Medium Enterprises (SMEs) in Sugihan Village, Tengaran District, Semarang Regency, through training in making digital brochures to promote educational tourism using the Canva application. This program was implemented in response to the lack of digital literacy and dependence on conventional promotions that limit the reach of the educational tourism market in Sugihan Village. The implementation method includes five stages: (1) analysis of the needs of SMEs and educational tourism, (2) preparation of digital brochure materials and designs, (3) training in making digital brochures, (4) implementation and mentoring, and (5) evaluation and continuous development. Participants were taught visual design techniques, persuasive content preparation, and distribution strategies through social media. The evaluation results showed a significant increase in the abilities of 25 participants: 75% were able to make independent digital brochures. It is hoped that after this training activity, it will have an impact on increasing tourist visits to Sugihan Village, Semarang Regency. Collaboration between academics from the University of Computer Science and Technology Lecturer team and the SME community also strengthens the sustainability of the program, with the formation of a digital working group to update promotional content regularly.